The Coronavirus Intervention in Ethiopia and the Challenges for Implementation - Nigussie, Hagos (Frontiers in Communication, 2021)
The coronavirus has been rapidly spreading across different nations globally. The pandemic will have a severe impact unless coordinated preventive measures are undertaken. This paper examines the COVID-19 intervention and the challenges for implementation in Mekelle city, Tigray, northern Ethiopia. A case study was used as a methodology. Telephone interviews, personal observation and document reviews were used as data collection techniques. Results of the study showed that the majority of the population in Mekelle city are aware of the pandemic. Handwashing with soap and water is mostly practiced. But there is a limited practice in physical distancing, notably, in religious institutions, market places, and coffee houses where a large number of people gather. Despite encouraging results, staying at home remains a challenge among the majority. Still, there is a belief that the pandemic is a ‘punishment from God’ while others believe that it is a disease of the ‘old’ and does not affect the young. Generally, implementing the COVID-19 intervention, mainly, the physical distancing seems challenging as the public continues to overlook government advice. As related studies such as the fight against Ebola outbreak in West African countries showed, this emanates from the lack of trust to media messages. In Tigray, religious leaders and community elders have a significant influence on their respective fellow members. Messages from these individuals remain trusted and can easily reach the majority due to social networks. This highlights that besides enforcing strict and prolonged measures from the government, reliable two-way communication can help to achieve the desired behavior change among different segments of the population. Hence, the COVID-19 intervention programs in Tigray should be designed and implemented in consideration of these factors. Empowering these individuals as communication agents could help to raise positive behaviors and prevention practices leading to collective action in the fight against the pandemic.